THE ISRAELI FACTOR IN IRAN-AZERBAIJAN RELATIONS (2005-2013) - ARMEN ISRAYELYAN (Banber Arevelagitut'yan Instituti, 2021)
The article deals with Israel’s factor which influences Iran-Azerbaijan relations. The article highlights the following issues when assessing the impact of the Israeli factor on Iran-Azerbaijan relations: • Represent Israel’s foreign policy priorities on Azerbaijan, • Assess the position of the Islamic Republic of Iran on Azerbaijan-Israel cooperation and analyze Iran's policy within this context, • Analyze Azerbaijan's motives for strengthening cooperation with Israel. The nuclear program, Iran's missile systems, the Shia factor, the Iranian-speaking peoples of Azerbaijan (Tats, Talish), the activities of Azerbaijani Shia opposition figures, the 760-kilometer border between Azerbaijan and Iran – these are the main factors underlying Israel's policy towards Azerbaijan. Azerbaijan first of all justified the establishment of relations with Israel with the expectation of receiving military-political assistance from Israel in the settlement of the Nagorno Karabakh conflict. During the presidency of Iranian President Mahmoud Ahmadinejad (2005-2013), when one of the scenarios for suspending Iran's nuclear program was considered a military attack, the territory of Azerbaijan was considered a platform for attacking Iran. While Baku has made every effort to exclude the Iranian factor in Azerbaijan-Israel military cooperation, the Iranian military-political management has always been skeptical of Baku's assurances, claiming that Israeli drones could easily be used for reconnaissance against Iran. • During Hassan Rouhani's presidency, as compared with Mahmoud Ahmadinejad's presidency, positive developments took place in the relations between Azerbaijan and Iran, and bilateral economic cooperation strengthened. In order to weaken Israel's influence in Azerbaijan, Iran replaced its policy of harsh response to Azerbaijan with economic cooperation. Iran was more concerned about the growing influence of Israel in various spheres in Azerbaijan than the use of a possible Israeli threat against Iran from the territory of Azerbaijan, which has always been raised in the past. • Azerbaijan tried to bring counterargument against Israel-Azerbaijan relations with Armenia-Iran relations. • In order to weaken Iran's religious influence, Azerbaijan, on the one hand, repressed the country's Shiite opposition figures, and on the other hand, Baku managed to obtain military-political support from Israel by exploiting the Iranian-Shiite "threat". • According to Iranian experts, the strategic relations between Azerbaijan and Israel have been established in the South Caucasus, in particular due to Iran's wrong policy towards Azerbaijan. • Currently, if in the Middle East, Iran more or less manages to control the threats appearing from the proxy war with Israel, than on its immediate border Iran is trying to avoid a direct confrontation with Israel. During the Second Artsakh War, the transfer of Israeli UVC of the territory of Iran, and in this regard, Iran's cautious statements are evidence of that.